Determination of Maximum Adsorption Capacity of Chitosan and Carboxymethyl Chitosan on the Absorption of Metal Ions Cr (VI) Based on the Langmuir Equation - Darwin Yunus Nasution; Amir Hamzah Siregar; Etika Rokhmayanti (Talenta Publisher, 2024)
A study has been conducted to investigate the adsorption of chrom (VI) metal ions by hand chitosan and carboxymethyl chitosan. This research aimed to examine the adsorption capacity of chitosan and carboxymethyl chitosan and determine the applicability of the Langmuir isotherm adsorption method for adsorbing Cr (VI) metal ions utilizing these materials. Chitosan was chemically treated with a 40% NaOH solution and monochloroacetic acid, dispersed in 2-propanol at room temperature for 10 h. This reaction resulted in the formation of carboxymethyl chitosan. FT-IR analyzed the functional group of carboxymethyl chitosan. The adsorption process was conducted using a standard solution with varying concentrations of Cr6+, specifically 5, 10, 15, and 20 mg/L. The concentration of Cr6+ adsorbed was measured using an Atomic Absorption Spectrophotometer. The findings demonstrated that carboxymethyl chitosan exhibited the maximum capacity for adsorbing chrom metal ions, with a mass of 0.9179 mg/g carboxymethyl chitosan at a concentration of 20 ppm. Chrom (VI) metal ion adsorption by carboxymethyl chitosan follows the Langmuir equation with an R2 value greater than 0.9. The maximum adsorption capacity of carboxymethyl chitosan is 1.16 mg/g, which is higher compared to chitosan's capacity of only 0.60 mg/g.